Adjusting the Energy Bands of WO3@ZnO Nanocomposite Heterojunction Through the Combination of WO3 Thin Film to Improve its Photoelectric Performance - Yan Xu (IEEE Access, 2020)
At present, nanomaterials with high-quality photoelectric properties are urgently needed to be used in the manufacture of solar cells. In this study, the hydrothermal synthesis method was first used to grow ZnO nanorod arrays, and then a layer of WO3 thin film with controllable thickness was prepared on ZnO nanorod arrays by magnetron sputtering, forming a series of WO3@ZnO nanocomposite heterojunction. We found that the value of the photocurrent of the prepared nanocomposite samples is nearly 30 times higher than WO3 films under illumination, and it is more stable. The results show that this controllable microstructure can further modify the surface properties of ZnO nanorods, and possess the high visible absorption and photoelectric conversion efficiency. By controlling the thickness of the WO3 film, the band can be regulated and ultimately optimized the photoelectrochemical properties of the composite structure.